Understanding Indigenous Exploitation Through Performance Based Research Funding Reviews in Colonial States - Love, Tyron R.; Hall, C. Michael (Frontiers in Research Metrics and Analytics, 2020)
Countries with significant indigenous populations, such as Australia, New Zealand and the Nordic countries, are providing increased support for improvements in the number of indigenous academics represented in higher education and engaged in research. Such developments have occurred at the same time as the implementation of performance-based research funding systems. However, despite the significance of such systems for academic careers and knowledge diffusion there has been relatively little consideration of the way within which they meet the needs of indigenous academics and knowledges. Drawing primarily on the New Zealand context, this perspective paper questions the positioning of Māori researchers and Māori research epistemologies (Kaupapa Maori) within the Performance Based Research Fund (PBRF) and the contemporary neoliberal higher education system. It is argued that the present system, rather than being genuinely inclusive, serves to reinforce the othering of Māori episteme and therefore perpetuates the hegemony of Western and colonial epistemologies and research structures. As such, there is a need to raise fundamental questions about the present ecologies of knowledge that performance based research systems create not only in the New Zealand higher education research context but also within other countries that seek to advance indigenous research.